A Multi-omics Approach Reveals the Effects of Bio- and Chemical- Pesticides on Rice Yield and Quality under Disease Stress - Chongchong Lu; Yingzhe Yue; Baoyou Liu; Yanke Jiang; Zimeng Li; Muhammad Zunair Latif; Xiaoying Zhang; Dayin Chen; Lili Dai; Lingguang Kong; Qian Du; Ziyi Yin; et al. (Rice)
Abstract Rice production is gravely threatened by bacterial leaf streak (BLS). BLS prevention and control rely heavily on chemical pesticides, which contaminate the environment and endanger human health. Here, we evaluated the effects of inducer of plant resistance ZhiNengCong (ZNC), which is derived from endophytic fungi Paecilomyces variotii, the chemical pesticide dioctyl diethylenetriamine (DDL) and the antibiotic pesticide zhongshengmycin (ZSM) on grain size and quality of diseased- rice (DR). BLS significantly reduced the thousand-grain weight and seed setting rate of rice plants, which could be restored by ZNC rather than DDL or ZSM. Transcriptome and metabolomics profiling showed that ZNC increased the expression levels of resistance-, growth- and sugars, amino acids and lipid metabolism-related genes in DR leaves and restored the levels of carbohydrates, vitamins, nucleotides and amino acids in DR grains, which is better than DDL and ZSM. This study demonstrates that plant immune inducers are more effective than conventional pesticides in restoring DR yield and quality, which provides novel insights into the innovation of green biopesticides in sustainable crop production.